Protective Effect of Garlic Oil Supplementation on Serum Sodium and Potassium Ions against Formaldehyde Induced Toxicity in Wistar Rats - Nihal, Insha; Maheshwari, Geeta; Singh, Surbhi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The present experimental study was designed to investigate the protective effect of garlic oil against formaldehyde vapor induced toxicity on serum electrolytes namely sodium (Na+) and potassium (K+). Twenty four male rats were randomly divided into three groups (control set 1, experimental set 2 and experimental set 3). The control set 1 was fed with standard food without any exposure and garlic oil supplementation while experimental set 2 was exposed to 6 ppm formaldehyde vapors for one hour daily for 30 days and experimental set 3 was given garlic oil supplementation (1 ml/100 g b. wt.) after exposure to 6 ppm formaldehyde vapors for one hour daily for 30 days. A highly significant increase in serum sodium ion level and a highly significant decrease in serum potassium ion level was observed respectively after exposure to formaldehyde vapors (P<0.01), while a significant decrease in serum sodium ion level (P<0.05) and a highly significant increase in serum potassium ion level has been noticed respectively after supplementation of garlic oil in comparison to formaldehyde vapor exposed rats (P<0.01). Therefore, it is concluded that garlic oil has shown positive potential to detoxify the toxic effect of formaldehyde inhalation on serum electrolytes sodium Na+ and potassium K+.